Total bacterial count as an attribute for raw milk quality - Markusson, Helena (SLU/Department of Molecular Sciences, 2021)
Milk is a nutritious food and at the same time a substrate where microorganisms thrive. Their metabolic impact can be useful in dairy fermentation, but the degradation of compounds within its habitat can also cause dairy food spoilage. The amount and type of bacteria directly affect the quality of the milk, in industry mostly evaluated by total bacterial count (TBC). TBC is an indicator of the hygienic conditions at farm level, as well as for the hygienic quality of the raw milk, where premium payment systems use TBC in the prizing of milk to the farmer. However, TBC merely gives the enumeration of bacteria in milk and not its microbial composition. Milk microbiota is today known to mainly consist of a few genera, but with high diversity and variations, thus the gap between TBC and milk microbiota has widened. Therefore, the aim in this literature study was to evaluate TBC as an attribute for milk quality and to relate TBC to alternative methods. Many factors related to farm management influence both bacterial counts and microbiota. Properly maintained hygiene and milk storing is of major importance from farm to dairy plant, and deviations cause bacterial counts to increase and contaminants with spoilage capacity to dominate. Correlations between TBC and bacteria of specific concern have been reported, although not consistently. TBC and psychrotrophic counts show similar dynamics, whereas thermotolerant bacteria are more frequent in milk with low total counts. Spoilage of pasteurized and ultra-high temperature processing (UHT) milk is mainly due to the heat-resistant enzymes produced by Pseudomonas, Acinetobacter and Bacillus. The numbers of these bacteria are of great importance for the industry in a milk production of high hygienic quality. Proteolytic activity is shown to have a relatively strong correlation with those bacteria and could thus be a more adequate indicator of milk quality, preferably evaluated close in time for processing. A focus on establishing alternative methods is needed to find more adequate indicators that meet dairy industry´s current needs.